Education, Media and Security: The Case of Nigeria - Iteogu, Odizuru; Jibowo, A. V. (NIU Journal of Social Sciences, 2019)
Without a carefully organized security system any entity (political or economic) would be in jeopardy. Without security, in its various forms, all developmental efforts would nose-dive into a nullity because security is necessary to safeguard all areas of socio-economic activity. Every developmental paradigm and design must fashion into it the element of security to ensure that all progress is not lost. That is our concern in this paper. That is an analysis of the relevance and promotion of security via education and the mass-media. We would realize that education permeates all sectors of the society. This is important because Nigeria needs to jealously guard and guide her common existence and the material success needed to sustain her in the years ahead. This paper has revealed that there is a common chord among the different components of socio-economic and political strides that links national security and eternal vigilance by citizens and agencies of state statutorily empowered to so do. These agencies spread across educational and media structures and organs. The citizens, acting in concert individually or as groups ought to join hands with the agencies of government to secure the developmental gains made in Nigeria since our political independence on October 1 st , 1960. The promotion of security must receive the greatest official and individual attention to ensure safety for all citizens through the instrumentality of education and effective media- driven enlightenment. Keywords: Education, Media, Security, Development, Case of Nigeria.